New tests of the distal speech rate effect: examining cross-linguistic generalization - Dilley, Laura; Morrill, Tuuli; Banzina, Elina (Frontiers in Psychology, 2013)
Recent findings [Dilley and Pitt, 2010. Psych. Science. 21, 1664-1670] have shown that manipulating context speech rate in English can cause entire syllables to disappear or appear perceptually. The current studies tested two rate-based explanations of this phenomenon while attempting to replicate and extend these findings to another language, Russian. In Experiment 1, native Russian speakers listened to Russian sentences which had been subjected to rate manipulations and performed a lexical report task. Experiment 2 investigated speech rate effects in cross-language speech perception; non-native speakers of Russian of both high and low proficiency were tested on the same Russian sentences as in Experiment 1. They decided between two lexical interpretations of a critical portion of the sentence, where one choice contained more phonological material than the other (e.g., /stərʌ'na/ “side” vs. /strʌ'na/ “country”). In both experiments, with native and non-native speakers of Russian, context speech rate and the relative duration of the critical sentence portion were found to influence the amount of phonological material perceived. The results support the generalized rate normalization hypothesis, according to which the content perceived in a spectrally ambiguous stretch of speech depends on the duration of that content relative to the surrounding speech, while showing that the findings of Dilley and Pitt (2010) extend to a variety of morphosyntactic contexts and a new language, Russian. Findings indicate that relative timing cues across an utterance can be critical to accurate lexical perception by both native and non-native speakers.